2020
DOI: 10.3389/fphar.2020.00195
|View full text |Cite
|
Sign up to set email alerts
|

Low Level Antibodies Against Alpha-Tropomyosin Are Associated With Increased Risk of Coronary Heart Disease

Abstract: Objective: Natural autoantibodies have been implicated to play a key role in the pathogenesis of coronary heart disease (CHD) because they augment autoimmune activation. The aim of this study was to identify novel specific autoantibodies of CHD, and analyze the relationship between their levels and CHD risk indicators.Approach and Results: First, clinical data and sera from CHD patients were collected. Then, one protein microarray containing 37 proteins that represent candidate autoantigens was developed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The expression levels of eight known CHD‐related proteins, including heat shock protein HSP 90‐alpha (HSP90AA1) (Sevim Bayrak et al , 2020; Xiao et al , 2020), malate dehydrogenase (MDH2) (Liu et al , 2014), MYL9 (Xiong et al , 2019), ACLY (Ference et al , 2019), N‐ethylmaleimide sensitive factor (NSF) (Mei et al , 2020), α‐tropomyosin gene (TPM) (Hirono et al , 2020; Zhang et al , 2020), SERPINE1 (Song et al , 2017), and complement factor H related 2 (CFHR2) (Zhang et al , 2016) were altered consistently in both groups. The protein expression levels of HSP90AA1, MDH2, MYL9, and ACLY were higher in the CHD group than those in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels of eight known CHD‐related proteins, including heat shock protein HSP 90‐alpha (HSP90AA1) (Sevim Bayrak et al , 2020; Xiao et al , 2020), malate dehydrogenase (MDH2) (Liu et al , 2014), MYL9 (Xiong et al , 2019), ACLY (Ference et al , 2019), N‐ethylmaleimide sensitive factor (NSF) (Mei et al , 2020), α‐tropomyosin gene (TPM) (Hirono et al , 2020; Zhang et al , 2020), SERPINE1 (Song et al , 2017), and complement factor H related 2 (CFHR2) (Zhang et al , 2016) were altered consistently in both groups. The protein expression levels of HSP90AA1, MDH2, MYL9, and ACLY were higher in the CHD group than those in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies that cross-react with PRKG1 may also alter calcium levels, thus affecting TPM function. For TPM1, cross-reactive Spike antibodies targeting the ELDKY motif may result in coronary heart disease, as low-level autoantibodies against this protein have been associated with increased risk for this condition [ 78 ] and TPM1 and TPM3 are cardiac disease-linked antigens [ 77 ]. Cardiac disease, including myocardial injury and arrhythmia, can be induced by SARS-CoV-2 infection [ 79 ] and myocarditis has been found to develop in some individuals following vaccination against SARS-CoV-2 [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies that cross-react with PRKG1 may also alter calcium levels, thus affecting TPM function. For TPM1, cross-reactive Spike antibodies targeting the ELDKY motif may result in coronary heart disease, as low-level autoantibodies against this protein have been associated with increased risk for this condition (Zhang et al, 2020) and TPM1 and TPM3 are cardiac disease-linked antigens (Marrama et al, 2022). Cardiac disease, including myocardial injury and arrhythmia, can be induced by SARS-CoV-2 infection (Nishiga et al, 2020) and myocarditis has been found to develop in some individuals following vaccination against SARS- CoV-2 (Patone et al, 2021).…”
Section: Resultsmentioning
confidence: 99%